Characterization of the evolutionary and virological aspects of mutations in the receptor binding motif of the SARS-CoV-2 spike protein - Masuda, Yuuka; Nasser, Hesham; Zahradnik, Jiri; Mitoma, Shuya; Shimizu, Ryo; Nagata, Kayoko; Takaori-Kondo, Akifumi; Schreiber, Gideon; , The Genotype to Phenotype Japan (G2P-Japan) Consortium; Shirakawa, Kotaro; Saito, Akatsuki; Ikeda, Terumasa; et al. (Frontiers in Virology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has substantially diversified during the pandemic, resulting in the successive emergence of variants characterized by various mutations. It has been observed that several epidemic variants, including those classified as variants of concern, share mutations at four key residues (L452R, T478K, E484K, and N501Y) within the receptor binding motif (RBM) region of the spike protein. However, the processes through which these four specific RBM mutations were acquired during the evolution of SARS-CoV-2, as well as the degree to which they enhance viral fitness, remain unclear. Moreover, the effect of these mutations on the properties of the spike protein is not yet fully understood. In this study, we performed a comprehensive phylogenetic analysis and showed that the four RBM mutations have been convergently acquired across various lineages throughout the evolutionary history of SARS-CoV-2. We also found a specific pattern in the order of acquisition for some of these mutations. Additionally, our epidemic dynamic modeling demonstrated that acquiring these mutations leads to an increase in the effective reproduction number of the virus. Furthermore, we engineered mutant spike proteins with all feasible combinations of the four mutations, and examined their properties to uncover the influence that these mutations have on viral characteristics. Our results provide insights into the roles these four mutations play in shaping the viral characteristics, epidemic proliferation, and evolutionary pathway of SARS-CoV-2.